Cryopreservation of cassava zygotic embryos and whole seeds in liquid nitrogen - Marín, M.L.; Mafla, G.; Roca, W.; Withers, Lyndsey A. (1990)
Cryopreservation in liquid nitrogen of isolated zygotic embryos and whole seeds of cassava have been studied. A simple method is proposed for utilization in germplasm conservation or other related uses. Very high percentage survival values (ca. 97 percent) of zygotic embryos and whole seeds were obtained by both slow and rapid cooling methods followed by slow thawing (1 hour at -70 degrees C followed by 1 hour at -15 degrees C). In the case of whole seeds, slow thawing prevented shattering. Recovery of whole plants occurred from all surviving seeds but was reduced to 25-34 percent for control and frozen embryos. This drop is attributed to physical injury during dissection. (AS)